Resentments in the cosmopolis: Anti-immigrant attitudes in postcolonial Singapore. (March 2020) - Dirksmeier, Peter
Abstract: This paper presents an analysis of the predictors of anti-immigrant attitudes in the postcolonial society of Singapore based on an examination of the impact of group threat on these resentments. The binary regression analysis finds that direct or parental immigration experience has a mitigating impact on anti-immigrant attitudes, while homophobia is the strongest predictor of anti-immigrant prejudice. However, the preference for Singaporeans over immigrants in the allocation of jobs during times of scarce work and low levels of trust in strangers reinforce anti-immigrant sentiments in Singapore. The outcomes presented in the paper suggest that group threat theory has only a moderate explanatory power and that feelings of mistrust deserve more attention in the future for explaining group-based hostile attitudes in plural contexts. Consequently, multicultural Singaporean society exhibits an attitudinal composition that corresponds only partly with group threat theory but with the assumption of the interrelatedness of prejudices. Highlights: An empirical analysis of anti-immigrant attitudes in Singapore with representative survey data is presented Group threat as a theoretical tool for analysing attitudinal trajectories in postcolonial societies is elaborated Perceived group threat has a moderate impact on anti-immigrant attitudes in Singapore Ethnic Chinese Singaporeans differ in less trusting strangers, but do not exhibit a higher risk of showing anti-immigrant attitudes